2015
DOI: 10.1016/j.molcel.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

IRGM Governs the Core Autophagy Machinery to Conduct Antimicrobial Defense

Abstract: SUMMARY IRGM, encoded by a uniquely human gene conferring risk for inflammatory diseases, affects autophagy through a hitherto unknown mechanism. Here we show how IRGM controls autophagy. IRGM interacts with ULK1 and Beclin 1 and promotes their co-assembly thus governing the formation of autophagy initiation complexes. We further show that IRGM interacts with pattern recognition receptors including NOD2. IRGM, NOD2 and ATG16L1, all of which are Crohn’s disease risk factors, form a molecular complex to modulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
207
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(223 citation statements)
references
References 48 publications
5
207
3
1
Order By: Relevance
“…It recently was found that in normal cells undergoing mitosis Golgi fragmentation is induced by AMPKα-dependent phosphorylation of GBF1 at T1337 (40,41). Another study showed that IRGM stimulates AMPKα by stabilization of the kinase in its T172 phosphorylated form (16). Hence, we examined the effect of siRNA-mediated depletion of IRGM on HCV-triggered phosphorylation of GBF1T1337 and AMPKαT172, phosphorylation events that mediate the activation of AMPK and GBF1.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…It recently was found that in normal cells undergoing mitosis Golgi fragmentation is induced by AMPKα-dependent phosphorylation of GBF1 at T1337 (40,41). Another study showed that IRGM stimulates AMPKα by stabilization of the kinase in its T172 phosphorylated form (16). Hence, we examined the effect of siRNA-mediated depletion of IRGM on HCV-triggered phosphorylation of GBF1T1337 and AMPKαT172, phosphorylation events that mediate the activation of AMPK and GBF1.…”
Section: Resultsmentioning
confidence: 96%
“…Human IRGM regulates autophagy (16) and has been identified as a risk factor for Crohn's disease and tuberculosis risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the related guanylate-binding protein and Mx gene families, they encode large GTP-binding proteins that function as dynamin-like proteins in mediating membrane remodeling and trafficking processes in cells (1)(2)(3)(4). In the absence of certain IRG proteins, alterations in membrane remodeling events have been observed, including the processing of pathogen-containing vacuoles (5)(6)(7)(8), vesicle formation and transport (4, 8 -12), cell motility (13,14), autophagy (15)(16)(17)(18)(19)(20), and mitochondrial fission (20,21). How these alterations relate to the dysfunctional immune responses displayed in IRG-deficient cells and mice in response to a variety of pathogens remains unclear.…”
mentioning
confidence: 99%
“…NOD2 enhances K63-linked ubiquitination of IRGM, enabling IRGM to interact with ULK1 and Beclin 1 (13). IRGM also stimulates autophagy by activating AMPK (13).…”
mentioning
confidence: 99%